Hemopatch to Fix Mobile Lobe after Thoracoscopic Lobectomy - Fiorelli, Alfonso; Carlucci, Annalisa; Cascone, Roberto; Santini, Mario (The Thoracic and Cardiovascular Surgeon, 2020)
Herein, we report a new technique of middle lobe fixation using Hemopatch after thoracoscopic right upper lobectomy. A 3–0 atraumatic polypropylene suture is passed first through the Hemopatch, then two not-inflated lobes, and then again patch. The lung is half-inflated, and the Hemopatch is placed onto the surface of the two half-inflated lobes in a bridging manner over the fissure. The suture is then tied by a clip. This procedure was successfully applied in five consecutive patients after thoracoscopic right upper lobectomy for cancer. No complications occurred during and after operation.
Keywords: lobar torsion; fixation; Hemopatch; video-assisted thoracoscopy surgery; lobectomy